2014
DOI: 10.1213/ane.0000000000000241
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in and Limitations of Cardiac Output Monitoring by Means of Electrical Impedance Tomography

Abstract: The hypothesis that EIT can be used to monitor CO and SV was confirmed, but further studies are required before this technique can be applied in clinical practice. HR was determined robustly and accurately. For SV monitoring, promising results were obtained in 80% of the experiments. However, unexpected scaling of the cardiac EIT signal causing inaccurate estimation of SV remains an issue. Before robust assessment of SV by EIT is suitable for clinical practice, the cause of and compensation for undesired scali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 32 publications
2
43
1
Order By: Relevance
“…Some studies describe limitations and challenges in cardiovascular EIT monitoring, in particular concerning the monitoring of SV. Patterson et al (2001) concluded the cardiac EIT signal depends strongly on electrode position, lung volume and posture, in healthy volunteers. In pig experiments, Pikkemaat et al (2014) observed variations in the subject-specific scaling of the cardiac EIT signal, which A c c e p t e d M a n u s c r i p t were interpreted to stem from lung volume or heart and belt position.…”
Section: Introductionmentioning
confidence: 96%
“…Some studies describe limitations and challenges in cardiovascular EIT monitoring, in particular concerning the monitoring of SV. Patterson et al (2001) concluded the cardiac EIT signal depends strongly on electrode position, lung volume and posture, in healthy volunteers. In pig experiments, Pikkemaat et al (2014) observed variations in the subject-specific scaling of the cardiac EIT signal, which A c c e p t e d M a n u s c r i p t were interpreted to stem from lung volume or heart and belt position.…”
Section: Introductionmentioning
confidence: 96%
“…These animals were kept in the current analyses, but a sensitivity analysis showed that the estimated reliabilities were not substantially affected by the inclusion or exclusion of these animals (see Web Appendix Part II). Note that the data for PEEP level 25 were included in the current analysis, as well as in the Pikkemaat et al study, although they were not explicitly mentioned in the latter.…”
Section: Case Studymentioning
confidence: 99%
“…were included in the current analysis, as well as in the Pikkemaat et al [8] study, although they were not explicitly mentioned in the latter. Figure 1 shows the individual profiles (gray lines) of ZSV as a function of measurement moment.…”
Section: Case Studymentioning
confidence: 99%
“…A promising technology to non-invasively and continuously monitor CO is electrical impedance tomography (EIT). EIT uses multiple bioimpedance measurements recorded from electrodes placed around the chest, and, generally, uses physics-based approaches to recover the conductivity, which has been shown to correlate well with SV in several studies [9,10,11]. We have been developing a wearable EIT system for continuous monitoring of CO with low power constraints and potential smart-phone compatibility [12,13].…”
Section: Introductionmentioning
confidence: 99%